Hot spot stability and change during the COVID-19 pandemic - Pearson, Roderick L. (Journal of crime and justice, 2025)
A fundamental law of criminology is that crime is concentrated in a small number of hot spots that remain stable over time. However, in light of the COVID-19 pandemic disrupting people’s daily routines through stay-at-home orders and social distancing restrictions, there is some doubt as to whether this law was briefly broken. This paper tests this proposition by examining the stability and growth of hot spots for assault, robbery, theft, burglary, and motor vehicle theft during the COVID-19 pandemic in Cincinnati, Ohio. The analysis revealed that less than 10% of street segments were responsible for the change in the overall crime trend for assault, robbery, and motor vehicle theft during the pandemic. In addition, over 40% of streets that were hot spots for assault and theft in 2018 and 2019 remained hot spots during the pandemic. However, there was an increase in street segments that became new hot spots as well. These street segments were 40–70% of all hot spots from 2020 to 2021. The findings of this paper indicate the spatial distribution of hot spots in Cincinnati changed during the pandemic as a notable percentage of hot spots went ‘cold’, resulting in significant fluctuations in crime in Cincinnati.